THE USE OF ORANGE (CITRUS SINENSIS) PEEL AS ANTIMICROBIAL AND ANTI-OXIDANT AGENTS - Ibri, K.; Bouhadi, D.; Hariri, A.; Meddah, B.; Tir Touil, A.; Ould Yerou, K. (University of Eloued جامعة الوادي, 2017)
Due to rapid growth of the food processing industry and the consumption of processed foods, the demand for natural antimicrobial agents is on the rise. Consumers have become more aware about the health effects of the synthetic preservatives used in food. Hence natural preservatives are developed to meet the demand of consumers. These natural antimicrobials are developed either from plants or their parts, animals or even microorganisms. Even the waste generated from the food industries is being considered as an alternative to produce natural antimicrobials. The aim of the present study was to utilize the waste generated from the citrus fruit processing (peel) industry. This study was to utilize the powder from the peel of Citrus sinensis in food (Oil of olive and cream dessert) to preserve their quality, this peel can be used as antimicrobial and antioxidant activity so food preservation purpose.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Citrus sinensis peel, powder, food, antimicrobial activity, antioxidant activity